Rancang Bangun Media Informasi Kampus Institut Teknologi Padang Berbasis Peta 3D Interaktif - Farhan Achyar; Wiki Lofandri (MASALIQ, 2026)
The development of web-based campus information media has encouraged the use of three-dimensional visualization, but the development of interactive 3D maps integrating manual low-poly modelling, baked lighting, and asset optimization under conditions of limited photogrammetric data remains limited. This study aims to design and evaluate an Institut Teknologi Padang campus information medium based on an interactive 3D map that is lightweight, responsive, and communicative. The study employed a research and development method using the Multimedia Development Life Cycle model, which comprises the concept, design, material collecting, assembly, testing, and distribution stages. Data were obtained through observation, documentation, spatial measurements, black-box testing, performance testing, and a User Acceptance Test questionnaire involving 36 respondents. The data were analyzed using quantitative descriptive analysis based on feasibility percentages. The results showed that the application of low-poly modelling, texture baking, Draco compression, and KTX2 textures reduced the asset size from more than 3.9 GB to less than 50 MB. All system functions were declared valid, while the average performance reached 160–164 FPS on the testing device. The feasibility test obtained a score of 87.13%, categorized as highly feasible, while the technical performance aspect reached 90.93%. These findings confirm that the integration of WebGL, Three.js, React, and Next.js is effective in supporting the development of interactive and efficient campus spatial information media. This study contributes to the development of web-based campus information media through a 3D asset optimization strategy suitable for environments with limited photogrammetric data. Future research should test the system on low-specification devices, expand the respondent coverage, and develop more adaptive navigation, route-searching, and camera-control features.